Does Greater Market Transparency Reduce Information Asymmetry?. Issue 11 (1st November 2016) - Lin, Yaling
ABSTRACT: This research aims to determine whether the degree of asymmetric information decreases with greater pre-trade transparency in the Taiwan stock market. We used the probability of informed trading based on the Markov regime-switching model in an order-driven auction market to investigate this topic. Information asymmetry showed no conspicuous variations with greater transparency. However, after further grouping, the empirical results revealed that increased transparency facilitated a decrease in information asymmetry in the sub-samples, which originally exhibited greater information asymmetry. In addition, the intraday patterns of probability of informed trading revealed that greater transparency facilitates decreased market information asymmetry after opening.